Koenigia hedbergii (Polygonaceae: Persicarieae), a distinct new species from Shennongjia National Nature Reserve, Central China - Li, Bo; Chen, Shaofeng; Li, Ya; Wang, Da-Xing; Du, Wei (Phytotaxa, 2016)
Koenigia hedbergii, a new and distinct species collected from the Shennongjia National Nature Reserve in the Northwest of Hubei Province (central China) is described and illustrated. The new species can be easily distinguished from other Koenigia species by its leaves lanceolate or lanceolate-ovate each showing 6–11 pairs of lateral veins and with distinct undulate margins, by its ocreae glabrous but sparsely puberulent at the bases, and achenes sharply trigonous with three pronouncedly keeled edges. A morphological comparison among the new species and the related ones, K. nepalensis and K. pilosa, is presented. The Koenigia-type pollen grains of the the new species were also observed and described.